Knowledge of Health Care Providers on HPV Related Issues in Cervical Cancer - Hussain, F; Flora, MS; Nahar, K; Khan, M (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Background: The field of cervical cancer prevention is rapidly evolving because of identification of Human Papilloma Virus (HPV) as the necessary cause of disease. HPV vaccines are now in the market. For successful triggering of cervical cancer prevention program, HPV informations should be communicated to health care providers whose understanding about HPV has lagged behind the scientific and technical advances. Objective: The objective of this intervention study was to identify gap and educate health care providers delivering services to women and adolescents in Medical Colleges on HPV related issues and vaccination. Methods: The study was done from July 2007 to June 2008 where 3 advocacy workshops were conducted. The knowledge level of 106 participants were assessed before and after intervention. Updated informations about HPV and vaccine was given to participants as intervention. Results: Wide knowledge gap was identified among participants on HPV related insues, but significant improvement was observed following intervention. The pretest and post test score of knowledge was 28.09 and 38.60 respectively showing an average increase of 10 after intervention. Conclusions: HPV education should be extensively disseminated to health care providers to obtain public health benefits of HPV vaccination program. DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11329 J Bangladesh Coll Phys Surg 2011; 29: 213-218